2012
DOI: 10.1177/0333102412466964
|View full text |Cite
|
Sign up to set email alerts
|

Axonal loss of white matter in migraine without aura: A tract-based spatial statistics study

Abstract: Given that decreased AD may suggest axonal loss, our findings may reveal axonal loss in MWoA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
106
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(124 citation statements)
references
References 35 publications
16
106
2
Order By: Relevance
“…The consistent results may suggest that the decreased ReHo in these regions is related with migraine. These brain regions with decreased ReHo in MWoA were similar to the brain regions reported in structural [21,22] and functional studies [5,17,2224] in migraine, which were mainly involved in pain-related processing [22]. In particular, decreased ReHo values in the rACC and the SMA were reported in a previous study [5].…”
Section: Discussionsupporting
confidence: 86%
“…The consistent results may suggest that the decreased ReHo in these regions is related with migraine. These brain regions with decreased ReHo in MWoA were similar to the brain regions reported in structural [21,22] and functional studies [5,17,2224] in migraine, which were mainly involved in pain-related processing [22]. In particular, decreased ReHo values in the rACC and the SMA were reported in a previous study [5].…”
Section: Discussionsupporting
confidence: 86%
“…26 However, most interesting, abnormalities of this region are also seen in other forms of chronic headache, such as migraine. 27,28 In fact, in nontraumatic migraine, abnormalities of the splenium are associated with a more chronic disease course, greater headache frequency, and comorbid neuropsychiatric conditions. 15 Lower values of PC 4 also corresponded to increased FA in the genu of the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…7,11 However, no studies have yet evaluated the role of white matter injury in the development of PTM, despite white matter injuries being seen with nontraumatic migraine, especially in the corpus callosum (CC). 12,13 Given increasing awareness of white matter injuries underlying nontraumatic migraine, we sought to determine whether there was a relationship between white matter injury and PTM in patients with mTBI. Previous studies have demonstrated that distinct white matter injuries after mTBI result in different and unique postconcussion symptoms, including sleep-wake disturbances, vestibulopathy, and ocular convergence insufficiency.…”
Section: 3mentioning
confidence: 99%